The performance and robustness of interest-rate rules in models of the euro area - Ramón Adalid; Günter Coenen; Peter McAdam; Stefano Siviero (European Central Bank (ECB), 2005)
In this paper, we examine the performance and robustness of optimised interest-rate rules in four models of the euro area which differ considerably in terms of size, degree of aggregation, relevance of forward-looking behavioural elements and adherence to micro-foundations. Our findings are broadly consistent with results documented for models of the U.S. economy: backward-looking models require relatively more aggressive policies with at most moderate inertia; rules that are optimised for such models tend to perform reasonably well in forward-looking models, while the reverse is not necessarily true; and, hence, the operating characteristics of robust rules (i.e., rules that perform satisfactorily in all models) are heavily weighted towards those required by backward-looking models.
Keywords: E31; E52; E58; E61; 330; euro area; macroeconomic modelling; Model uncertainty; monetary policy rules; Robustness; Geldpolitik; Zinspolitik; Regelbindung versus Diskretion; Geldpolitisches Ziel; Theorie; Eurozone; EU-Staaten